ETHNO-CULTURAL VALUES AS A FACTOR SHAPING CONSUMER ECONOMIC BEHAVIOR (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
In the modern globalized world, consumer behavior is not only influenced by economic factors (income, prices, inflation) but is also closely tied to cultural, social, and ethnic values. Ethno-cultural values are a system of values derived from the historical, cultural, religious, and social traditions of a particular ethnic group. These values significantly influence consumer decision-making, shaping purchasing habits, brand loyalty, and overall economic behavior.